Lies across America what our historic sites get wrong - Loewen, James W. 1942-2021 (Simon & Schuster, 2000)
"Offers startling revelations about sites we think we know; Valley, Forge, Abraham Lincoln's log cabin, the Intrepid. It also tells of new sites, events, and individuals that should be commemorated on the landscape but are't; a tombstone with a story to tell in Mississippi, a spy in the confederate White House, the unforeseen fallout from the first nuclear missile test, the reverse underground railway, a modern "sundown" town (blacks can work there,j but they'd better leave before the sun sets). It asks why, across our landscape, Indians are consistently "savage", tribal names are wrong and derogatory, whites "discover" everything, and the term "massacre" is a one-way street; why war museums have selective memories, guides at FDR's family mansion in Hyde park are "specifically forbidden" to talk about Roosevelt's mistresses, and James Buchanan's house denies that he was gay. It muses about the Civil War mare in Kentucky who got an extra body part, the Polynesian King made to look like a Roman emperor on monuments in Hawaii, and the statue of a conquistador in New Mexico who lost his foot."
Keywords: Geschichte; Historic sites -- United States; Monuments -- United States; Mythos; Topografie; USA; United States -- History -- Errors, inventions, etc